Pengaruh Promosi, Persepsi Nilai, dan Kemudahan Akses Layanan terhadap Minat Menggunakan Produk Bank Mandiri - Carla Tousalwa; Harry A.P. Sitaniapessy (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the effects of promotion, perceived value, and service accessibility on students’ intention to use banking products. The research was conducted using a quantitative approach with a survey method involving 198 students from the Department of Business Administration and Accounting at Politeknik Negeri Ambon. Respondents were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with statistical software. The results indicate that promotion, perceived value, and service accessibility have positive and significant effects on intention to use banking products. Promotion and perceived value show stronger influences compared to service accessibility. These findings suggest that students’ intention to use banking products is shaped by integrated marketing communication, evaluation of benefits and costs, and operational convenience of services. This study contributes to the marketing and banking literature by extending the integrated marketing strategy perspective in explaining customer intention. Practically, the results provide insights for banks in designing relevant promotional strategies, strengthening product value, and improving service accessibility to enhance adoption among young consumers.Keywords: promotion; perceived value; service accessibility; intention to use; banking.